2021
DOI: 10.1159/000516187
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Crescents Affects Prognosis of IgA Nephropathy in Patients without Obvious Chronic Renal Pathology

Abstract: <b><i>Introduction:</i></b> A working group on the Oxford classification of IgA nephropathy (IgAN) recently reported that crescents detected in the kidney tissue predicted a worse renal outcome. However, the effect of C1 lesion (crescents in &#x3c;1/4th of all glomeruli) and their volume on the prognosis of IgAN is still unclear. We explored the association of C1 lesion with the renal prognosis in IgAN patients without obvious chronic renal lesions (glomerulosclerosis &#x3c;25%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Low serum levels of complement C3 is often associated with poor renal outcomes in IgAN [ 23 ]. Consistent with our previous study, global crescent and Serum C3 are the independent risk factor for IgAN progression and poor renal outcome in IgAN patients without significant chronic kidney damage [ 24 ]. Further more, Latest study show that crescent is independently associated with higher mortality in IgAN [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Low serum levels of complement C3 is often associated with poor renal outcomes in IgAN [ 23 ]. Consistent with our previous study, global crescent and Serum C3 are the independent risk factor for IgAN progression and poor renal outcome in IgAN patients without significant chronic kidney damage [ 24 ]. Further more, Latest study show that crescent is independently associated with higher mortality in IgAN [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study showed that, complement hyper-activation may be involved in the development of extra-capillary proliferation, notably diffuse crescent formation, in these patients (33). More recently, volume of crescents was investigated by Lin et al, to evaluate the prognosis of IgAN in individuals without chronic morphologic lesions on renal biopsy (35). This study included 305 biopsy-proven IgAN patients.…”
Section: Significance Of Crescents In Igan (Mest-c Scores)mentioning
confidence: 83%
“…On multivariate analysis, the GC group was associated with an increased risk (HR = 2.756, 95% CI = 1.068-7.109) of adverse outcome. They concluded that global crescents can be an independent risk factor for the development of progressive kidney failure in IgAN (35). In summary, Oxford classification of IgAN has proved to be an independent and earlier risk stratification parameter for patients with IgAN and when combined with clinical and laboratory features at the time of diagnosis, it can achieve accurate risk assessment two years earlier than methods used in current clinical practice.…”
Section: Significance Of Crescents In Igan (Mest-c Scores)mentioning
confidence: 99%
“…They are more often hypertensive, have higher levels of serum creatinine (with lower eGFR), higher levels of proteinuria, and more advanced renal disease at biopsy (i.e., GS and SS and IFTA) [14,20,26,29,31]. As a result, it has been shown that they are 1.5-3.0 times more likely to progress to ESKD compared with patients without crescents [8,13,14,29,30]. Not unexpectedly, the prognosis in IgAN patients with crescents is related to the proportion of glomeruli with crescents.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in our study, overall, crescents involve ≤25% of glomeruli in 20-40% of patients with only 2-14% of patients having lesions in >25% of glomeruli [13,15,[23][24][25][26], while the presence of crescents involving ≥50% of glomeruli is an even more infrequent, seen in <2% of patients with IgAN [21,27,28]. While the poor prognosis associated with "diffuse crescents" has been well demonstrated, it has now been shown that the presence of crescents in even a smaller proportion of glomeruli can portend a poor prognosis [8,13,14,29,30].…”
Section: Discussionmentioning
confidence: 99%